Identification of a small‐molecule ligand of β‐arrestin1 as an inhibitor of stromal fibroblast cell migration accelerated by cancer cells. (29th January 2018) - Suvarna, Kruthi; Honda, Kaori; Kondoh, Yasumitsu; Osada, Hiroyuki; Watanabe, Nobumoto
Abstract: Stromal fibroblasts, which occupy a major portion of the tumor microenvironment, play an important role in cancer metastasis. Thus, targeting of these fibroblasts activated by cancer cells (carcinoma‐associated fibroblasts; CAFs) might aid in the improved treatment of cancer metastasis. NIH3T3 fibroblasts cocultured with MCF7 cells displayed enhanced migration compared to NIH3T3 fibroblasts cultured alone. We used this system to identify the small‐molecule inhibitors responsible for their enhanced migration, a characteristic of CAFs. We selected β ‐arrestin1, which showed high expression in cocultured cells, as a molecular target for such inhibitors. Cofilin, a protein downstream of β ‐arrestin1, is activated/dephosphorylated in this condition. The small‐molecule ligands of β ‐arrestin1 obtained by chemical array were then examined using a wound healing coculture assay. RKN5755 was identified as a selective inhibitor of activated fibroblasts. RKN5755 inhibited the enhanced migration of fibroblasts cocultured with cancer cells by binding to β ‐arrestin1 and interfering with β ‐arrestin1‐mediated cofilin signaling pathways. Therefore, these results demonstrate the role of β ‐arrestin1 in the activation of fibroblasts and inhibiting this protein by small molecule inhibitor might be a potential therapeutic target for the stromal fibroblast activation (cancer–stroma interaction). Abstract : NIH3T3 fibroblasts cocultured with MCF7 cells displayed enhanced migration compared to NIH3T3 fibroblasts cultured alone. Using this system, we identified RKN5755, a selective inhibitor of activated fibroblasts. This small molecule binds to β ‐arrestin1 and interferes with β ‐arrestin1‐mediated cofilin signaling pathways.